Wel of niet NEET? De complexiteit van de transitie van onderwijs naar arbeidsmarkt in Brussel - Géraldine André; Andrew Crosby (Brussels Studies)
In the wake of the European Union's recommendations, the public authorities in Brussels have put strategies in place to combat early school leaving and youth unemployment. Nevertheless, these programmes aimed at the “NEET” category (not in education, employment or training) have a standardised approach and end up reducing the problem to a question of individual employability. This paper presents a critical analysis of the NEET category, which we propose to break down into several subcategories, whose use in Brussels public policies would allow a better targeting of the young people who need it most. Based on ethnographic material collected from young people in the working-class neighbourhoods of Brussels, we propose a sociological approach which allows us to identify a more refined typology of NEET/non-NEET situations. Our analysis contributes to deconstructing the statistical category of NEET into diversified social situations, and shows how much NEET situations are the result of paths shaped by structural dynamics as well as by processes of inequality, whether they are related to class and/or migratory origin.